EFEKTIVITAS INTERPRETATIVE STRUKTURAL MODELING (ISM) DALAM MENGANALISIS FAKTOR PENGHAMBAT MINAT BELAJAR SISWA DI KELAS XI IPS SMA ADABIAH 2 PADANG - Lismawati, Nurda; khairani, Khairani (JURNAL BUANA, 2024)
This study aims to determine the inhibiting factors for student interest in class XI at SMA Adabiah 2 Padang. This type of research is qualitative, using the ISM (Interpretative Structural Modeling) method. The results obtained explain the findings related to factors inhibiting student interest in learning. The research subjects are curriculum representatives, homeroom teachers, and class XI IPS with a total sample of 5 people. then input to the ISM software later there will be the final results in the table in the form of structures and graphics. The results of this study are to find out the most important factor / urgent inhibiting interest in learning for class XI students of SMA Adabiah 2 Padang is the influence of gadgets which is located at level 3 and on the graph is located at independent.